Iterative Frequency Domain Equalization and Carrier Synchronization for Multi-Resolution Constellations, - Pedrosa, Pedro (2018)
Broadband broadcast and multicast wireless systems usually employ OFDM modulations (Orthogonal Frequency Division Multiplexing) combined with non-uniform hierarchical constellations. However, these schemes are very prone to nonlinear distortion effects and have high carrier synchronization requirements. SC-FDE (Single-Carrier with Frequency-Domain Equalization) is an attractive alternative for OFDM, especially when an efficient power amplification is intended. In this paper we consider the use of SC-FDE schemes combined with non-uniform hierarchical constellations in broadband broadcast and multicast wireless systems. We study the impact of residual CFO (Carrier Frequency Offset) on the performance of multi-resolution schemes and we propose iterative frequency domain receivers with joint detection and carrier synchronization to cope with residual CFO estimation errors (a coarse CFO estimation and compensation is assumed before the equalization procedure). Our results show that while a very high carrier synchronization accuracy is required for the least protected bits, the most protected bits are relatively robust to the CFO. By employing the proposed receiver we increase significantly the robustness to residual CFO estimation errors